EUPHEMISM AND DYSPHEMISM STRATEGIES IN DONALD TRUMP’S SPEECH AT SOTU 2020 - Lutvia Nurul Kafi; Agwin Degaf (International Journal of Humanity Studies (IJHS), 2021)
In this article, the researchers aim to explain the types and functions of the use of expressions of euphemism and dysphemism in President Donald Trump's speeches at the State of the Union Address 2020. With Donald Trump's controversial background and many of his statements attracting attention, researchers assume that Trump uses many expressions of euphemism and dysphemism in his speech. This study uses Allan's and Burridge's (1991) theoretical framework on euphemism and dysphemism as the base for data analysis. This study's data were taken from Trump's utterances in his speech. This study uses a qualitative descriptive research method to carry out in-depth analysis. The results of this study indicate that there are eight types of euphemistic expressions, five types of dysphemism, eight functions of euphemisms, and six functions of dysphemism.